Fertility intentions in the era of the new three-child policy in China: a cross-sectional survey of married adults of reproductive age - Zhang, Chenyun; Zhou, Yingying; Ke, Yujing; Zhang, Wenchang; Qin, Mengqi; Alias, Haridah; Wong, Li Ping (Frontiers in Public Health, 2025)
BackgroundChina’s fertility rate has declined to an estimated record low of 1.09 in 2022, resulting in widespread broad negative impact on society and poses challenges for China’s economy. This study aimed to examine the fertility intentions of married adults under the new three-child policy and to investigate how demographic characteristics, support services, and perceived costliness and affordability of childbirth and childrearing influence these intentions.MethodsA large-scale web-based cross-sectional survey was carried out from 30 August 2021 to 1st May 2022. Study participants were married adults of reproductive age (18 to 49 years old) and Chinese citizens. The primary outcome was fertility intention. Factors associated with fertility intention namely (1) satisfaction with reproductive, maternal, newborn, and child health (RMNCH) services or support, and (2) affordability in childbirth and childrearing were collected.ResultsA total of 2,996 complete responses were received in the survey. The desire for ≥ 3 children was 11.2%. Participants from the eastern region recorded the lowest proportion of desire for ≥ 3 children (8.2%). By demographics, males, lower educational achievement, sub-urban residency were significantly associated with higher intention to have ≥ 3 children. The association between perceived costliness of childbirth and childrearing cost and intention to have ≥ 3 children was not significant. A lower level of perceived affordability was significantly associated with a higher intention to have ≥ 3 children [adjusted odds ratio (aOR) = 1.63, 95% confidence interval (CI) 1.15–2.30]. Satisfaction with RMNCH services or support has no significant influence on fertility intention.ConclusionFindings revealed that higher educational qualifications and urbanization are associated with lower fertility intention. Cost and support services may not be the main reasons driving low fertility desire.